Energy efficiency: A study of energy consumption pattern in UUM Campus - Chandrakusuma, Azra Nugraha; Mohd Shafie, Shafini (2019)
The fact that generation of energy is still highly depend on fossil fuels, the huge amount of carbon emissions release into the air as it relates with the high-level consumption of electricity. Regarding the concerns about the effects of climate change has stimulated to lowering the energy consumption and implement the energy management. With energy management, it could help in reducing the energy consumption and conserve the energy resources that are depleting categorized as non-renewable energy that we are very depend on. The objectives of this paper is to analyze the pattern of energy consumption in UUM Campus building. The data that have been used for this study is from primary and secondary data. Primary data have been collected by expert interview and secondary data derived from electronic sources and book. Finding of this study pointed out that by implementing sustainable strategies and policy, it could help Universiti Utara Malaysia undergo the energy management and aim to reduce overall energy consumption in the Campus.